Addition of sequences counting functions of two variables based on polynomial splines - Приставка, П.О. (Proceedings of National Aviation University, 2007)
This article is the solution of practical research of the polynomial splines of two variables based on the B-splines that, on average, are related to the interpolar. These splines allow us to get simple calculating schemes which are convenient for the practical application.